A novel withanolide with an unprecedented carbon skeleton from Physalis angulata. Issue 5 (18th January 2017) - Sun, Cheng-Peng; Kutateladze, Andrei G.; Zhao, Feng; Chen, Li-Xia; Qiu, Feng
Abstract : Aromaphysalin A (1 ), possessing an exceptional C(11)–C(15) bond and a rearranged 4, 9-cyclized aromatic ring, is isolated from of Physalis angulata . Abstract : A novel withanolide, aromaphysalin A (1 ), possessing an exceptional C(11)–C(15) bond and an unprecedented 4, 9-cyclized aromatic ring (ring A), is isolated from stems and leaves of Physalis angulata L. Its structure was determined by a combination of HRESIMS, 2D NMR spectra, and theoretical calculations. Compound1 exhibited inhibitory activity on NO production with an IC50 value of 51.64 μM. A plausible biosynthetic pathway for1 is also discussed.